Autonomic reactivity as function of anxiety level and mode of stimulus presentation - Yegge, William E.; Barrientos, Guido A. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Thirty-two snake-phobic female subjects participated in a study to assess the efficacy of using imaginary, as opposed to in-vivo, phobic stimuli in eliciting a conditioned GSR. It was predicted that high-anxious (H A ) Ss would be more responsive than low-anxious Ss to the imaginary mode of presentation as used in desensitization. Ss were divided into four groups on the basis of manifest anxiety level (M AS) and order of stimulus presentation. Statistical analyses indicated differential GSR responsivity to the imagination of a phobic stimulus as a función of MAS level.